Effects of Mesenchymal Stem Cell‐Derived Paracrine Signals and Their Delivery Strategies. Issue 7 (12th January 2021) - Chang, Calvin; Yan, Jerry; Yao, Zhicheng; Zhang, Chi; Li, Xiaowei; Mao, Hai‐Quan
Abstract: Mesenchymal stem cells (MSCs) have been widely studied as a versatile cell source for tissue regeneration and remodeling due to their potent bioactivity, which includes modulation of inflammation response, macrophage polarization toward proregenerative lineage, promotion of angiogenesis, and reduction in fibrosis. This review focuses on profiling the effects of paracrine signals of MSCs, commonly referred to as the secretome, and highlighting the various engineering approaches to tune the MSC secretome. Recent advances in biomaterials‐based therapeutic strategies for delivery of MSCs and MSC‐derived secretome in the form of extracellular vesicles are discussed, along with their advantages and challenges. Abstract : This review discusses various engineering approaches to tune the effects of paracrine signals secreted by mesenchymal stem cells (MSCs), commonly referred to as the secretome. Recent advances in biomaterials‐based therapeutic strategies for delivery of MSCs and MSC‐derived secretome in the form of extracellular vesicles are discussed along with their advantages and challenges.